Financial Constraints and Organizational Conditions: Explaining Work Stress and Performance - Niki Puspita Sari; Helmi Muhammad; Arini Ro’ikhatus Salsabila (RISK : Jurnal Riset Bisnis dan Ekonomi, 2026)
Financial constraints in private educational institutions are often considered a barrier to organizational effectiveness. However, a new perspective suggests that financial constraints actually stimulate performance. This study aims to examine the influence of financial constraints, work environment, organizational culture, and job stress on performance in private educational institutions. Using a quantitative approach, data for this study was collected through a survey of teachers and education personnel at 28 private kindergartens in Malang Regency. The data were analyzed using multiple regression analysis to examine the relationships between variables. The findings indicate that financial constraints, work environment, and organizational culture significantly contribute to improved performance, while job stress has no effect. Interestingly, financial constraints are not recognized as structural barriers but rather serve as challenges that actually enhance performance. This study contributes to the literature on organizational behavior in resource-constrained institutions by integrating financial constraints with organizational and psychological factors in explaining employee performance.